Identifying the causes of excessive weight gain in early childhood - Permana, Dwinda Abi; Saenko, Mariia (Universitas Negeri Yogyakarta, 2025)
The growing health hazards associated with obesity and excess weight, particularly in young children, have made efforts to avoid these issues a top priority. By employing a cross-sectional research design, this study seeks to determine the reasons for weight growth in young children. Fifty children served as research subjects. Multivariate analysis was the method of analysis employed. The study's findings indicated a substantial (p <0.05) correlation between early childhood weight gain and variation factors. According to the study's findings, early childhood weight growth was associated with nutrition, parental genetics, and a lack of physical exercise. The growing health hazards associated with obesity and excess weight, particularly in young children, have made efforts to avoid these issues a top priority. This research was conducted in early childhood education and kindergartens in Kediri, East Java. Purposive sampling was used, meaning the sample was selected based on specific considerations, namely those who were overweight or obese. By employing a cross-sectional research design, this study seeks to determine the reasons for weight growth in young children. Fifty children served as research subjects. Multivariate analysis was the method of analysis employed. The results of the study were that the hereditary factor variable obtained a percentage of 56% with a p value of 0.045 which indicates p < 0.05 proving that there is a significant relationship between hereditary factors and weight gain. The dietary pattern variable accounted for the highest percentage, at 62%, with a p-value of 0.023, indicating a p < 0.05, demonstrating a significant relationship between dietary patterns and weight gain in early childhood. The final variable was physical activity, accounting for 54%. The p-value was 0.027, indicating a p < 0.05, indicating a significant relationship between physical activity and weight gain. The conclusion of this study is that the variables of poor dietary management and lack of daily physical activity are factors that have a higher risk of weight gain.